The paradigm of «Being» in Ontology and Metaphysics - Banda Marroquín, Obdulio Italo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The linguistic structure «being», which philosophy handles as an alleged noun, derives from archaic and polysemous verbal forms, which determines the semantic emptiness of the alleged noun «being». This is neither a noun nor a concept, nor a principle: it is a flatus vocis. Ontology and metaphysics, in order to fill the conceptual gaps in their respective systems, have been forced to hypostatise or ontologise what is a simple verbal structure: «being».
Keywords: «Being»; ἐὸν; ontology; metaphysics; εἰμί